La política y lo político en Twitter: Análisis del discurso de los candidatos presidenciales de Colombia (2023)
The new virtual social networks operate as spaces for debate, these are fundamental to understanding contemporary electoral processes. Although the strategic effectiveness of the networks is not proven, since they depend on multiple contextual elements, their characteristics and particularities have assumed progressively greater relevance in the context of the social and behavioral sciences analysis, while they are inserted in the speeches and practices of candidates, advisory teams and political parties. In this paper, discourses of candidates for the presidency of Colombia (2018), which take place on Twitter, are analyzed, demonstrating the way in which they shape the construction of a political dimension. Based on a netnographic study, a documentary corpus of tweets is interpreted, issued by four presidential candidates, classified from five categories of analysis (Corruption, education, health, unemployment and peace). © AISTI 2018.